A bilevel game matching algorithm in cellular-D2D hybrid scenario - Tian YAO; Hui ZHANG (Dianxin kexue)
With the rapid development of wireless technologies,wireless access networks enter the 5G system phase.5G environment with various technical scenarios is heterogeneous and dynamic,causing great challenges for wireless resource management.Hence,it is significant to achieve the optimal matching between network resources and user demands.Therefore,wireless resource matching algorithms in 5G environment have become one of the hottest research directions.A bilevel game matching algorithm in cellular-D2D hybrid scenario was proposed:a QoE based matching model considering user fairness was constructed,the bilevel matching game theory was used to solve this optimization problem,and the effectiveness of proposed algorithm was verified through simulations.